A comparative study of hair shafts in scalp psoriasis and seborrheic dermatitis using atomic force microscopy. Issue 1 (4th January 2012) - Kim, Kyung Sook; Shin, M. K.; Ahn, J. J.; Haw, C. R.; Park, Hun‐Kuk
<x xml:space="preserve">Abstract</x> Background As the inflammatory scalp conditions share similar clinical manifestations of scaling, inflammation, and pruritus, the differential diagnosis of these lesions; especially between scalp psoriasis (SP) and seborrheic dermatitis (SD) is sometimes difficult. Objectives The aim of this study was to investigate the differences on the hair surface in SP and SD for a clinical diagnosis, using atomic force microscopy (AFM). Methods The hair shafts of 14 patients and 28 patients with SP and SD respectively, were taken from the lesional region. Hairs from healthy adults not having any hair diseases were also examined in the same way for the controls. Surface characteristics of SP and SD‐affected hair shafts such as, pitting, scale thickness, and roughness, were observed on the AFM images. Results One hundred percentage and four percentage of the patients with SP and SD respectively had macropits on their hair shafts. In both the SP and SD‐affected hairs, the scale thickness was more than 4‐fold than that in the control hairs. The surface of SP‐affected hairs was rougher than that of SD‐affected and control hairs. Conclusion The differences in hair shafts between SP and SD were investigated noninvasively using AFM. The presence of macropits could be helpful in the differentiation between SP and SD.